Differential Association of Dietary Linoleic Acid and Alpha-linolenic Acid with Adipose Tissue in a Sample of Iranian Adults; A Cohort-based Cross-sectional Study: - Masoumi, Seyed Jalil; Mohit, Mohsen; Karami, Esmail; Hadi, Saeid (Galen Medical Journal, 2023)
Background: Overweight and obesity are the most critical risk factors for chronic diseases. The quality of dietary fatty acids as one of the factors affecting fat accumulation has received little attention. This study investigates the association between dietary linoleic acid (LA) and alpha-linolenic acid (ALA) with body fat indices in a sample of healthy Iranian adults. Materials and Methods: In this cohort-based cross-sectional study, 3,195 individuals aged 20 to 60 who participated in the Shiraz University of Medical Science Employees Health Cohort study were included. Dietary intake was assessed using a validated 118-item Food Frequency Questionnaire (FFQ), and body composition was assessed by the bioelectrical impedance analysis method. Multiple linear regression adjusted for relevant confounders was used to determine the associations. Results: Mean dietary intake of LA was 14.20 ± 7.01 mg/day for men and 13.90 ± 6.71 mg/day for women. Additionally, the daily intake of ALA was 0.18 ± 0.18 mg/day in men and 0.17 ± 0.19 mg/day in women. Dietary intake of ALA for men had an inversely significant association with body fat mass (BFM) (β: -0.585, 95% CI: -1.137, -0.032, P=0.038), percentage of body fat (PBF) (β: -0.537, 95% CI: -0.945, -0.129, P=0.010), Visceral Fat Area (VFA) (β: -2.998, 95% CI: -5.695, -0.302, P=0.029), and Waist to Hip Ratio (WHR) (β: -0.689, 95% CI: -1.339, -0.040, P=0.038). Conclusion: Higher dietary ALA intake was associated with lower BFM, BFP, VAF, and WHR in men. The present study confirms that ALA intake should be considered a preventive treatment to improve body composition. However, further research is recommended in this regard.